Peran Mediasi Innovation Capability dalam hubungan Knowledge Sharing dan Innovation Performance pada UMKM di Rokan Hilir - Anita, Nur (Akuntansi & Ekonomika, 2023)
This research aims to test the impact of knowledge sharing on innovation performance mediated, by innovation capability. The study used a survey method with 76 participants of MSMEs in the Rokan Hilir district. Research data is processed using WarpPLS 7.0. Research results show that knowledge sharing has a positive influence on innovation capability and innovation capacity mediates the relationship between knowledge sharing and innovation performance. This research contributes to providing empirical evidence as well as new insights into the importance of knowledge-sharing behavior coupled with the ability to innovate in improving MSME’s performance. A good performance of MSMEs will help UMKM to survive in the long term and have competitiveness so that MSME’s goal of “Naik Kelas” is achieved.